Flood Mitigation-Based Settlement Environment Management Strategy in Hudi Laran Region, Dili, Timor Leste - Elizino Ferreira; Henry Feriadi; Winarna (Global Writing Academica Researching & Publishing, 2023)
Geographically located hudi laran area the residential environment is in a flood-prone area because of its presence below the surface of the highway, so it requires a strategy of spatial arrangement based on disaster mitigation as an effort to safety and comfort the local community. Hudi Laran area has become a flood subscription at the time of rain because the topography is flat and sunken then water runoff from the hill will drain the water to a lower place. The main causative factor of flooding is that the channels that receive water flow are damaged and covered by soil and irregular land use. In this study using a qualitative descriptive approach with data collection techniques through observations, interviews, questionnaires and documentation conducted directly by researchers, for the processing of data needed data obtained through the results of interviews with respondents. The results of the analysis are processed using qualitative analysis methods and displayed in the form of diagrams that will explain the results of interviews with respondents. Then processed data analysis results are done by summarizing the results of the interview and then displayed in the form of paragraphs. Based on the results of the analysis data, the conclusion is the main factor causing flooding, namely high rainfall and damage to channels to the main / primary drainage that cause flooding with an average water level intensity of 50-70 cm and a maximum height of 70-100cm. Community participation in cleaning the channels that have been built by the government is expected to suppress smaller flood disasters.